Small Scale Trials: Implementation of Mobile Learning Applications for Badminton Materials - Silvi Aryanti; Novritika Novritika; Fitriana Fitriana; Destriana Destriana; Samsul Azhar; Nurpajriwati Nurpajriwati; Yunda Anisa (Altius: Jurnal Ilmu Olahraga dan Kesehatan, 2022)
This study aims to determine the results of small-scale trials of research products, namely mobile learning applications for basic badminton techniques. This research is a continuation of previous research, namely the research product has been validated by experts and then in the next stage, namely conducting product trials on a small scale. Respondents in this study were 14 students of the Physical and Health Education Study Program, Faculty of Teaching and Education, Sriwijaya University. Small-scale trials are carried out by displaying mobile learning applications while learning takes place. This research is research and development by adopting Borg & Gall's theory only to small-scale trials. Based on the results of small-scale trials implementing mobile learning applications, namely 85.6% in the feasible category. The implication of this research is that mobile learning application research products are suitable for use for learning because they can be downloaded without being constrained by time and space.